Interleukin‐27 promotes inflammatory and neuroprotective responses in microglia. Issue 1 (20th January 2013) - Kawanokuchi, Jun; Takeuchi, Hideyuki; Sonobe, Yoshifumi; Mizuno, Tetsuya; Suzumura, Akio
Abstract Objectives Interleukin‐27 (IL‐27) is released by antigen‐presenting cells including macrophages, dendritic cells and microglia, and negatively regulates IL‐17‐producing T helper (Th17) cells, which play key pathogenic roles in multiple sclerosis. As the effects of IL‐27 on cells in the central nervous system are unclear, we have examined the effects of IL‐27 on microglia to uncover the roles of IL‐27 in immune responses of the central nervous system. Methods The effects of IL‐27 on microglial production of cytokines, neurotrophic factors and antigen‐presentation related molecules were examined using reverse transcription polymerase chain reaction analyses and enzyme‐linked immunosorbent assays. The effects of IL‐27 on microglial antigen‐presenting function were also assessed using coculture assays of microglia and myelin oligodendrocyte glycoprotein peptide 35–55‐specific T cells. Results We showed that IL‐27 induces inflammatory and neuroprotective responses effects in microglia. IL‐27 enhanced the production of nitric oxide and such pro‐inflammatory cytokines as tumor necrosis factor‐α and IL‐6 in lipopolysaccharide‐activated microglia; these effects were not observed in unstimulated microglia, suggesting that IL‐27 acts as an amplifier rather than an initiator of microglial neuroinflammation. IL‐27 also enhanced microglial antigen presentation to promote Th1 polarization and suppress Th17 cell development by increasing IL‐12 levels and reducing IL‐23 levels. Furthermore, IL‐27 increased microglial production of nerve growth factor, glial cell line‐derived neurotrophic factor and brain‐derived neurotrophic factor. Conclusions Our data suggest the therapeutic potential of IL‐27 and microglia for multiple sclerosis through Th17 cell suppression and neurotrophic factor production.